Parameter Control System of Aeroponic Method on Plants Based on Internet of Things (IoT) - Zahran, Dzaki; Yolanda, Desta; Purbolingga, Yoan (CHIPSET, 2025)
The Internet of Things (IoT)-based Aeroponic System is an innovation in the cultivation of crops, especially potatoes, on limited land. This research aims to design an aeroponic parameter control system that integrates real-time measurement of temperature, humidity, and pH to improve the efficiency and productivity of urban agriculture. The system uses the ESP32 as the main data processor, with a DHT11 sensor for temperature and humidity measurements, as well as a pH sensor for nutrient regulation. Automation is carried out through relays and control modules connected to the Blynk app for remote monitoring and control. Tests show that this system is able to maintain the stability of the growing environment with an average parameter error of less than 5%. The system offers sustainable solutions for urban agriculture, reducing water consumption, and overcoming the limitations of narrow land.